Perioperative Outcomes of Acute Type-A Aortic Dissection Repair was Unaffected by COVID-19 Testing Delay - Orelaru, Felix; Norton, Elizabeth L; Ahmad, Rana-Armaghan; Naeem, Aroma; Kim, Karen M; Fukuhara, Shinichi; Patel, Himanshu J; Deeb, G Michael; Yang, Bo (Cardiology and Cardiovascular Medicine, 2022)
Background: This study assesses impact of COVID-19 testing delay on perioperative outcomes of Acute Type A Aortic Dissection (ATAAD) repair at a single institution. Methods: From January 2010 - May 2021, 539 ATAAD patients underwent open aortic repair at our institution. Sixty-five of these patients had open aortic repair during COVID (March 2020 - May 2021) and 474 patients were pre-COVID (January 2010 - February 2020). Results: Compared to the pre-COVID group, patients During-COVID had a higher proportion of previous myocardial ischemia [9/65 (14%) vs 28/474 (5.9%), p=0.03], chronic obstructive pulmonary disease [14/65 (22%) vs 55/474 (12%), p=0.02], and renal malperfusion syndrome [11/65 (17%) vs 30/474 (6.4%), p=0.01]. There was no significant difference in surgical outcomes between groups, including operative mortality (7.6% vs 9.2%, p=0.64). The median admission-to-Operating Room (OR) time was 107 minutes in the During-COVID group compared to 87 minutes in pre-COVID group, p=0.88. During COVID, the median admission-to-OR time was significantly longer in the Waiting group compared to the No-waiting group (209 min vs 75min, p=0.0009). Only one patient had positive COVID test. There were no aortic ruptures while awaiting COVID testing results. There was a total of 6 reported deaths in the During-COVID group: 1 patient died post-surgery due to ARDS caused by COVID, and others due to ischemic stroke (3 patients) and organ failure (2 patients). Conclusions: Perioperative outcomes of ATAAD patients were similar during-COVID compared to pre-COVID. Waiting for COVID testing results did not significantly affect the perioperative outcomes among ATAAD patients after repair.